Spectrum of Disorders Leading to Sudden Cardiac Death - Gilani, Sayed Tanveer Abbas; Khan, Dilshad Ahmed; Iftikhar, Ghazala; Khan, Kumail Abbas; Rauf, Amer; Siddiqui, Abdul Hameed (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine the frequency of disorders leading to sudden cardiac death (SCD). Study Design: Cross-sectional study. Place and duration of study: Pathology Lab in collaboration with the Cardiology Department, AFIC & NIHD, Rawalpindi Pakistan, from Jan 2017 to Dec 2018. Methodology: A total of 305 cases of sudden cardiac death reported within the last 24 hours of a death to AFIC Rawalpindi were included consecutively. Cases with a history of extracardiac diseases leading to sudden death were excluded. Most of the included cases were diagnosed phenotypically based on clinical examination, biochemistry, ECG, echocardiography, angiography, thallium scan, electro-physiological studies, cardiac CT scan, MRI and routine autopsy whenever recommended. Results: Out of 305 cases, 197 (65%) were males and 108 (35%) females. Disorders leading to SCD were found in 178 (58.3%) cases due to ischemic heart disease (IHD), aortic dissection (0.7%), hypertrophic cardiomyopathy (HCM) (0.3%), dilated cardiomyopathy (DCM) (10.5%), congenital heart disease (12.1%) and valvular heart disease (7.9%). While in cardiac channelopathies, catecholaminergic polymorphic ventricular tachycardia (CPVT) in 5 (1.6%) and congenital long QT syndrome (LQTS) in 2 (0.7%) cases. However, 24 (7.9%) cases remained as sudden unexplained deaths (SUD). Conclusion: In our setup, ischemic heart disease and dilated cardiomyopathy were the commonest causes of sudden cardiac death, followed by congenital heart disease and valvular heart diseases.